Francisella–Arthropod Vector Interaction and its Role in Patho-Adaptation to Infect Mammals - Abu Kwaik, Yousef; Akimana, Christine (Frontiers in Microbiology, 2011)
Francisella tularensis is a Gram-negative, intracellular, zoonotic bacterium, and is the causative agent of tularemia in a broad host range. Arthropods such as ticks, mosquitoes, and flies maintain F. tularensis in nature by transmitting the bacteria among small mammals. While the tick is largely believed to be a biological vector of F. tularensis, transmission by mosquitoes and flies is largely believed to be mechanical on the mouthpart through interrupted feedings. However, the mechanism of infection of the vectors by F. tularensis is not well understood. Since F. tularensis has not been localized in the salivary gland of the primary human biting ticks, it is thought that bacterial transmission by ticks is through mechanical inoculation of tick feces containing F. tularensis into the skin wound. D. melanogaster is an established arthropod-vector model of tularemia, where F. tularensis infects hemocytes, and is found in hemolymph, as seen in ticks. In addition, phagosome biogenesis and robust intracellular proliferation of F. tularensis in arthropod-derived cells are similar to that in mammalian macrophages. Furthermore, bacterial factors required for infectivity of mammals are often required for infectivity of the fly by F. tularensis. Several host factors that contribute to F. tularensis intracellular pathogenesis in D. melanogaster have been identified, and F. tularensis targets some of the evolutionarily conserved eukaryotic processes to enable intracellular survival and proliferation in evolutionarily distant hosts